HIGH ORDER THINKING SKILLS-BASED QUESTIONS IN THE TEST ITEMS DEVELOPED BY SENIOR HIGH SCHOOL ENGLISH TEACHERS OF PADANG - Nurul Afifah Ramadhana; Yenni Rozimela; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
This research was a descriptive research that aimed to identify the tests developed by senior high school English teachers in Padang using High Order Thinking Skills criteria. This study also aimed to determine the mostly-used criteria of HOTS in the tests. The sample in this study were mid semester tests and semester tests developed by English teachers from MGMP Bahasa Inggris SMA kota Padang. The tests used in this study were from grade XI of 2016/2017. Each test had two packages (A and B). This study used instrument in the form of indicators from HOTS criteria and Bloom’s HOTS criteria.               From the result of the tests developed by senior high school English teachers of Padang using the criteria of Higher Order Thinking Skills, it showed that the tests developed had used the HOTS criteria. As a result of the analysis of the two tests, 30% of High Order Thinking Skills questions were found in the tests. The result of this research also found that the mostly-used HOTS criteria in the tests are Creating and Deduction. The Knowledge dimensions found in the tests are Conceptual Knowledge, Procedural Knowledge, and Metacognitive Knowledge.